Pengaruh Penambahan CMC (Carboxy Methyl Cellulose) Pada Pembuatan Sirup Sirih Cina (Peperomia pellucida L. Kunth) Jahe Putih (Zingiber officinale) Terhadap Karakteristik Fisik dan Sensoris - Zulfahmi, A.Nova; Jumisah, Jumisah; Dwi Hastuti , Ningrum; Cholid, Irfan; Indriawan, Rois (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
The aim of this research was to determine the effect of adding CMC (Carboxyl Methyl Cellulose) on the characteristics (physical and sensory) of Chinese betel syrup. This research was conducted at the TEFA Lab, and the Sensory Laboratory of the Department of Agriculture and Business, Ketapang State Polytechnic, from April 2024 to July 2024. The research used the addition of CMC (0%, 0.25%, 0.50%, 0.75%). The parameters observed include physical characteristics (viscosity) and organoleptic tests (hedonic tests including aroma, taste and color). The research results showed that the CMC addition treatment had a significant effect on viscosity and organoleptics (hedonic taste test). C3 treatment (addition of 0.50% CMC) was the best treatment.